2022
DOI: 10.3390/jcm11092499
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of McGrath Videolaryngoscope versus Macintosh Laryngoscope for Nasotracheal Intubation: A Systematic Review and Meta-Analysis

Abstract: Background: In this study, it was shown that the routine use of McGrath videolaryngoscopy may improve intubation success rates. The benefits to using a videolaryngoscope in nasotracheal intubation were also demonstrated. However, no solid evidence concerning the effectiveness of the use of McGrath videolaryngoscopes in nasotracheal intubation has previously been reported. As a result, we questioned whether, in adult patients who underwent oral and maxillofacial surgeries with nasotracheal intubation (P), the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…The available variety will be limited due to prices; nevertheless, departments of anesthesiology might be harshly judged when a dangerous airway event occurs and is investigated in light of new guidelines [ 36 ]. Our results show consensus with previous systematic reviews and meta-analyses [ 37 , 38 ] showing that this improvement is more noticeable in patients that have a complex airway [ 39 ] and that endorse the usage of video laryngoscopes to accomplish successful intubation in patients that have a greater complex laryngoscopy risk [ 40 ].…”
Section: Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…The available variety will be limited due to prices; nevertheless, departments of anesthesiology might be harshly judged when a dangerous airway event occurs and is investigated in light of new guidelines [ 36 ]. Our results show consensus with previous systematic reviews and meta-analyses [ 37 , 38 ] showing that this improvement is more noticeable in patients that have a complex airway [ 39 ] and that endorse the usage of video laryngoscopes to accomplish successful intubation in patients that have a greater complex laryngoscopy risk [ 40 ].…”
Section: Reviewsupporting
confidence: 90%
“…The results of this review also indicated an increase in the degree of classification from the Cormack-Lehane classification system after using VL as compared to Mac laryngoscopy, which recommends the visualization of the glottis using the VL technique. This finding is also supported by another systematic review and meta-analysis [ 37 ].…”
Section: Reviewsupporting
confidence: 82%
“…The direct laryngoscopy (DL) is the most widely used method to perform ETI; notably, it might a challenging learning curve [7,8], and the proficiency with DL deteriorates over time if not routinely practiced [9]. Alternatively, video laryngoscopes (VLSs) have improved the visualization of the vocal cords [10], with improved results suggested both in any setting [11] as well as in challenging scenarios such as cardiac arrest [12] or nasotracheal intubation [13]. Moreover, the VLS technique has recently shown better performance than DL in a large multicentric randomized controlled trial conducted mostly in the emergency department setting [14].…”
Section: Introductionmentioning
confidence: 99%